Case report: Headache and neurological deficits with CSF lymphocytosis (HaNDL) associated with P/Q type voltage-gated calcium channel antibodies (CACNA1A). (August 2020) - Adib-Samii, Poneh; Little, Simon; Vincent, Angela; Nirmalananthan, Niranjanan
Background: Headache and Neurological Deficits with cerebrospinal fluid (CSF) Lymphocytosis (HaNDL) is an increasingly recognised syndrome but the aetiology remains unclear. HaNDL has striking clinical features similar to Familial Hemiplegic Migraine (FHM), commonly related to gene mutations encoding the P/Q-type voltage-gated calcium channel (VGCC). Case report: We report a case of HaNDL associated with high P/Q-type voltage-gated calcium channel antibodies. Extensive investigations excluded alternative diagnoses and CSF lymphocytosis resolved within 3 months. The case was complicated by raised intracranial pressure resulting in an enlarged blind spot, papilloedema and bilateral lateral rectus palsies. Conclusion: This novel association of P/Q-type voltage-gated calcium channel antibodies with HaNDL has implications for the pathology of HaNDL and spectrum of voltage-gated calcium channel-antibody disorders. We compare the clinical features of FHM and HaNDL and the potential pathological role of these antibodies. This case also highlights that raised intracranial pressure is a common feature of HaNDL, rarely resulting in serious complications.